MISIONAL EKLESIOLOGI BUDAYA DIGITAL: MENGURAI TANTANGAN GEJALA TRANSHUMANIS DAN CYBORG - Tony Salurante (Phronesis: Jurnal Teologi dan Misi, 2023)
Not only philosophy, ethics, and other fields but also ecclesiological life are facing severe challenges from the impact of digital culture, which continues to develop endlessly. This context encourages the church to think further about something new to predict what will happen and how it should take its role. This article offers a diachronic mission approach examining current and future contexts. The church is a missionary whose identity is to present the values of the Kingdom of God for His glory. This research indicates that the development of digital culture will be contrary to the Christian faith. This digital world is a context that God allows to occur to prepare for life in the church; every believer understands the challenges of transhumanists and cyborgs around them.